Bibliometric Review: Current Trends and Future Direction of Public Sector Budgeting - NURUL SHUHADA MOHD GHARIB; CHE RUHANA ISA; ZAKIAH SALEH; AHMAD TAJUDIN (Asian Journal of Accounting Perspectives, 2024)
Research aim: This study conducts a bibliometric analysis to delve into the current state and future direction of public sector budgeting globally by scrutinising the overall publishing patterns and knowledge landscape surrounding the evolution of public sector budgeting research. Design/ Methodology/ Approach: A bibliometric analysis technique was employed to study the development of scientific publications about public sector budgeting. The Scopus database was selected as the main database, and all the data were collected as of November 3, 2023. The first stage involved identifying all relevant documents from the Scopus database. Inclusion and exclusion criteria resulted in a total of 1,925 documents within the period between 1913 to November 3, 2023. The bibliometric analysis of public sector budgeting yielded significant insights into publication patterns, influential literature, notable authors, highly referenced works, and prevalent themes within this domain. Research finding: This analysis reveals a consistent growth in published material over time, with the United States emerging as the primary contributor in terms of volume. Distinguished scholars like Hou Yilin and Richard J. Cebula have made substantial impact, garnering noteworthy citations for their contributions. Moreover, the review outlines prominent themes in public sector budgeting, underscoring the multifaceted nature of research within this crucial area. Practitioner/ Policy implication: The study findings offer valuable perspectives for researchers, practitioners, and policymakers, enhancing comprehension of the challenges and prospects in public sector budgeting. Furthermore, longitudinal studies tracking the evolution of themes and trends in public sector budgeting over time could offer valuable insights into the changing landscape of budgetary practices in the public sector. Additionally, comparative studies across different countries and regions could provide a more nuanced understanding of the diverse approaches to public sector budgeting and the factors influencing budgetary practices in various contexts. Research limitation: The analysis was based on a specific set of data from the Scopus database, and therefore, might not capture all publications in the field of public sector budgeting. Additionally, the review focuses on quantitative analysis of publication trends and citations; thus, the qualitative aspects of the included works are not fully explored. Furthermore, the study is limited to the available data and might not encompass the most recent publications in the field.